(3GdMhGTj GdCRgQjI aj Md CdaGX GdebOeI GdLRQjIs - (3NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO GdLQLGhqj GdCRgQj, Rjf GdOjf, hcGf jYQa HGdhbGO , J (B905 (3g` s
(3ChdgG (B:s
(3CeG HYO aEf ef Chdi eG JUQa ajg Gdgee GdYhGd cdGe Gddg GdcHjQ GdeJYGd, hCge eG ojHJOC Hg JLhjO MQhag hJMSjf CdaGXg s
(3BNQgG (B:s
(3hGdfXe LeY GdCTjGA Ydi gjFI eJfGSHI hbhdg JbOeg Cj JMaI hgOjI hNJegG HGdMeO hGdUdGI dJchf ejehfI ddEaJJGM hGdENJJGe s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1800s
Keywords: (3GdbQGAGJ hGdJLhjOs